The Projection of Development : Cinematic Representation as A(nother) Source of Authoritative Knowledge? - Lewis, David (Taylor and Francis, 2013)
Popular representations of development need to be taken seriously (though not uncritically) as sources of authoritative knowledge, not least because this is how most people in the global North (and elsewhere) ‘encounter’ development issues. To this end, and building on the broader agenda presented in a previous article exploring the usefulness of literary representations of development, we consider three different types of cinematic representations of development: films providing uniquely instructive insights, those unhelpfully eliding and simplifying complex processes, and those that, with the benefit of historical hindsight, usefully convey a sense of the prevailing assumptions that guided and interpreted the efficacy of development-related interventions at a particular time and place. We argue that the commercial and technical imperatives governing the production of contemporary films, and ‘popular’ films in particular, generate a highly variable capacity to ‘accurately’ render key issues in development, and thereby heighten their potential to both illuminate and obscure those issues.